A solar based system for integrated production of power, heat, hot water and cooling - Gursoy, Mehmet; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
Renewable energy sources have gained great importance in meeting the increasing energy demands in today's world and reducing the environmental impacts, such as greenhouse gas emissions, particularly caused by traditional fossil fuel sources. In this study, a unique integrated energy system driven by solar power is proposed. In order to achieve poly-generation, a concentrated solar power tower system is integrated with a Rankine cycle, an organic Rankine cycle, an absorption cooling system, greenhouses, and a water heating system. The proposed system is designed to generate power, hot water, cooling, and heating for residential buildings and greenhouses. The system analysis is performed in terms of thermodynamics using energy and exergy principles, and then both energy and exergy efficiencies are used to assess the system's overall performance. Through parametric studies, the effects of changing various operating parameters and conditions on performance are examined. The energy and the exergy efficiencies for the overall system are found to be 22.64% and 21.8%, respectively.
Keywords: Energy; Exergy; Efficiency; Solar energy; Renewable energy; Thermal energy storage; Thermodynamics; Energy & Fuels